2014
DOI: 10.1016/j.sbspro.2014.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of Malaysian Green Hotels and Resorts

Abstract: Recently there has been a tremendous effort in greening the tourism industry due to its negative environmental impacts. The efforts of greening the lodging industry in M alaysia is growing slowly due to several barriers. The aim of this study is to determine the barriers of green hotels and resorts in M alaysia. This study employed qualitative method using in depth interview of the case studies. Five case studies were chosen. The findings identified 12 barriers. The barriers are categorized under significant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 16 publications
3
60
0
Order By: Relevance
“…The challenges parameters were prepared through content analysis of few studies such as (Eric S W Chan, 2011;Yusof & Jamaludin, 2014) The parameters are tested using five points Likert Scale ranging from 1= Strongly Disagree to 5= Strongly Agree. Questionnaires were distributed to 100 operators on the four Marine Park Islands and 85 operators did response.…”
Section: Sample and Methods Of Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges parameters were prepared through content analysis of few studies such as (Eric S W Chan, 2011;Yusof & Jamaludin, 2014) The parameters are tested using five points Likert Scale ranging from 1= Strongly Disagree to 5= Strongly Agree. Questionnaires were distributed to 100 operators on the four Marine Park Islands and 85 operators did response.…”
Section: Sample and Methods Of Data Collectionmentioning
confidence: 99%
“…Some of the examples are: challenges of sustainable facility management in Nigeria by (Ikediashi, Ogunlana, Oladokun, & Adewuyi, 2013), challenges of organization in implementing green marketing strategies by (Ramirez, 2010), challenges to implementing EMS in organization by (Kirkland & Thompson, 1999), challenges in adopting EMS by all type of SMEs (C. McKeiver, 2005) and challenges in implementing environmental practices in tourism industry (Chan, 2008;Graci, 2006;Yusof & Jamaludin, 2014). However, studies regarding challenges faced by SME tourism operators in Malaysia are very limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it also emphasises on materials and products associated with lower content and emissions of hazardous materials and gases, materials and products with longer life-span, suppliers with environmentally-preferable technologies and practices, and environmentally-sustainable or preferable alternatives for commodities (Sears & Bromwich, 2016). Yusof and Jamaludin (2014) reported that financial barriers are among the obstacles to the GT implementation as GT products are deemed expensive and that there is lack of manpower and equipment in GT projects which results in adverse risk takers. Nevertheless, the agenda is reflected in the Federal budget which allocated RM1.5 billion into the Green Technology Financing Scheme (GTFS) in the 2010 budget and increased to RM2 billion between (Green Building Index, 2015.…”
Section: Green Policy Integrationmentioning
confidence: 99%
“…The green technology provides many benefits including enhancing occupants' health and comfort, improving indoor air quality, reducing Carbon dioxide emission and minimising maintenance and operating cost (Amanjaya Specialist Centre, 2015). Conclusively, GT has relatively low demand due to the lack of understanding about its products and services, lack of experts along the value chain and difficulty in balancing service quality with environmental performance (Yusof & Jamaludin, 2014). Moreover, hospital operators give low priority over the various initiatives as there are only eleven GBI-certified hospitals, as of August 2016 (Ng, 2016).…”
Section: Best Practices In Malaysia Us and Canada: Where Should Malamentioning
confidence: 99%
“…In this regard, Malaysia represents one of 12 mega diverse countries in the world, which have abundant of floras and faunas (Yusof & Jamaludin, 2014). According to Malaysia Tourism Minister Y.B Dato Sri Dr Ng Yen Yen in 2012, "Malaysia is currently recognized by the UNWTO as the world 9th most travelled destination in the world.…”
Section: Introductionmentioning
confidence: 99%